Applied Sciences to the Study of Technical Historical Heritage and/or Industrial Heritage - Rojas Sola, José (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book presents a sample of theoretical and practical advances in applied sciences in the study of technical historical and/or industrial heritage. It covers several applications, such as geometric modelling and virtual reconstruction, computer-aided design and kinematic simulation, history of manufacturing, digital techniques in industrial heritage areas, building efficient management models, proposal for heritage intervention in a BIM environment, three-dimensional modelling using unmanned aerial vehicle imagery, computer-aided design, computer-aided engineering, and multi-criteria cataloging of the immovable items of industrial heritage. The contributions included in this book describe the state-of-the-art advances in this field and indicate the potential of studies of technical historical or industrial heritage in multidisciplinary applications in the fields of engineering and architecture.